Alfalfa - Johnson, Henry George (My University, 1896)
Introduction: Alfalfa belongs to the botanical family called Leguminosae. The family is so called because its fruit are in legumes or pods, with from one to several seeds in a pod. Peas and beans are the best types of this family. It belongs to the genus Medicago while the other clovers are of the genus Trifolium, three leaved, its full name is Medicago Salvia. The generic name is derived from the Greek Medike, and refers to the fact that the Greeks obtained it from the far east probably Media in Asia, thus showing that it is of a very ancient origin being traced back to the ancient kingdoms of Media and Persia. It was brought to Greece during the Persian wars in 470 B.C. and from thence it has continued westward in its course following civilization, a sit were in its westward flow. It is known to have been cultivated by the Romans for some length of time.
Citation: Johnson, Henry George. Alfalfa. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Botany; Alfalfa; Leguminosae; History; Medicago; Theses; Manuscripts (documents)